Modified genetic algorithm based power allocation scheme for amplify-and-forward cooperative relay network. (July 2018) - Gachhadar, Anand; Hindia, MHD Nour; Qamar, Faizan; Siddiqui, M. Hassam Shakil; Noordin, Kamarul Ariffin; Amiri, Iraj S
Abstract: Cooperative relay (CR) is a favorable technique to provide better spectral efficiency and enhance the cell coverage area in a cost-effective manner. However, several undesired issues, such as high-power consumption, arise due to use of a high number of relay nodes (RNs) in the network, Moreover, in a dynamic environment, full channel state information (CSI) is not always available. Therefore, all RNs need to calculate the abrupt changes in the channel; otherwise, the overhead delay will increase and the RNs will consume higher network power. To address this, an optimized modified genetic algorithm (Modified GA) based scheme is proposed that utilizes probabilistic selection rules and fitness scores. The results are presented in terms of symbol error rate (SER), network capacity, power consumption, and power improvement in order to analyze the performance of the proposed scheme. The results show that the proposed scheme provides better overall performance as compared to conventional optimization approaches.